Altering the bacterial community: sour soup decreased CO2 production and improved the fermentation quality of Broussonetia papyrifera, Tritriale and mixed silages - Qiming Cheng; Qiming Cheng; Qiming Cheng; Dianpeng Liu; Yao Lei; Maoya Li; Yulian Chen; Jiachuhan Wang; Xiangjiang He; Yuanyuan Zhao; Chao Chen; Xiaoqing Zhang; et al. (Frontiers in Microbiology, 2025)
IntroductionCarbon dioxide (CO2) generated during the ensiling process is a source of greenhouse gas emissions and a reason for the loss of nutrients during ensiling.MethodsBroussonetia papyrifera (B), Tritriale (T) and their mixtures (B7T3, B5T5 and B3T7) were ensiled with sour soup (S) and Lactobacillus acidophilus (LAB) to investigate the effects of additives on silage quality, CO2 production and bacterial communities.ResultsAfter 45 days of fermentation, the B3T7 treatment resulted in the lowest CO2 production, a relatively high lactic acid content (pH < 4.2), and relatively high relative abundances of Lactiplantibacillus and Weissella after fermentation; the quality of silage in all the treatments with additives was greater than that in the CK treatment, and the CO2 content was significantly lower than that in the CK treatment (P < 0.05). In addition, the overall silage quality was better than that of CK after the addition of additives, the CO2 content was significantly lower (P < 0.05), and adding sour soup resulted in a greater effect than adding LAB. CO2 production was positively correlated with the relative abundances of Lactococcus, Enterococcus, and Neoscardovia and negatively correlated with the relative abundances of Lactiplantibacillus, Weissella, and Sphingomonas.ConclusionsIn summary, selecting an appropriate proportion of different forages for mixed silage and adding sour soup may be effective ways to improve silage quality and reduce CO2 production during ensiling.